Effect of Nano-Carbon on Water Holding Capacity in a Sandy Soil of the Loess Plateau (2017)
The poor water retention capacity of sandy soils commonly aggregate soil erosion and ecological environment on the Chinese Loess Plateau. Due to its strong capacity for absorption and large specific surface area, the use of nanocarbon made of coconut shell as a soil amendment that could improve water retention was investigated. Soil column experiments were conducted in which a layer of nanocarbon mixed well with the soil was formed at a depth of 20 cm below the soil surface. Four different nanocarbon contents by weight (0%, 0.1%, 0.5%, and 1%) and five thicknesses of the nanocarbon- soil mixture layer ranging from 1 to 5 cm were considered. Cumulative infiltration and soil water content distributions were determined when water was added to soil columns. Soil Water Characteristic Curves (SWCC) were obtained using the centrifuge method. The principal results showed that the infiltration rate and cumulative infiltration increased with the increases of nanocarbon contents, to the thicknesses of the nano carbon-soil mixture layer. Soil water contents that below the soil-nano carbon layer decreased sharply. Both the Brooks-Corey and van Genuchten models could describe well the SWCC of the disturbed sandy soil with various nano carbon contents. Both the saturated water content (θs), residual water content (θr) and empirical parameter (α) increased with increasing nano carbon content, while the pore-size distribution parameter (n) decreased. The available soil water contents were efficiently increased with the increase in nanocarbon contents.